2022
DOI: 10.3389/fmed.2022.814606
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Lung: Geriatric Conditions Afflict Community-Dwelling Older Adults With Self-Reported Chronic Obstructive Pulmonary Disease

Abstract: RationaleChronic obstructive pulmonary disease (COPD) predominantly affects older adults. However, the co-morbid occurrence of geriatric conditions has been understudied.ObjectiveCharacterize the prevalence of geriatric conditions among community-dwelling U.S. older adults with self-reported COPD.MethodsWe conducted a nationally representative, cross-sectional study of 3,005 U.S. community-dwelling older adults (ages 57–85 years) from the National Social Life, Health, and Aging Project (NSHAP). We evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…COPD mostly affects older adults, and the development of multimorbidity may complicate COPD management. 30 People living with COPD have almost twice the risk of heart failure and myocardial infarction when compared with those without COPD belonging to the same age, sex, race, and education level. 30 Even COPD patients with no history of cardiovascular disease have a higher risk of cardiovascular complications, such as myocardial infarction and stroke, following a moderate exacerbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD mostly affects older adults, and the development of multimorbidity may complicate COPD management. 30 People living with COPD have almost twice the risk of heart failure and myocardial infarction when compared with those without COPD belonging to the same age, sex, race, and education level. 30 Even COPD patients with no history of cardiovascular disease have a higher risk of cardiovascular complications, such as myocardial infarction and stroke, following a moderate exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“… 30 People living with COPD have almost twice the risk of heart failure and myocardial infarction when compared with those without COPD belonging to the same age, sex, race, and education level. 30 Even COPD patients with no history of cardiovascular disease have a higher risk of cardiovascular complications, such as myocardial infarction and stroke, following a moderate exacerbation. 14 We showed that cardiovascular comorbidities are a major risk factor for death in Italian patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Close and cohabiting relationships may also affect the presence or absence of loneliness, but this association is not always straightforward. Witt et al [55] explored prevalence of geriatric conditions among 3005 community dwelling older adults. People with self-reported COPD (10.7% of the sample) reported more social disengagement and greater loneliness than people without COPD.…”
Section: Partners and Informal Carersmentioning
confidence: 99%
“…In addition to the physiological consequences, physical activity avoidance has consequences in terms of participation in social interactions. This further contributes to the development of mental health problems as well as social isolation and loneliness [ 8 ].…”
Section: Introduction: Copd a Disease With Extrapulmonary Consequencesmentioning
confidence: 99%